ANALYSIS OF CHANGES IN THE URBAN SPACE OF GUARIROBA-TAQUARITINGA-SP, USING GEOTECHNOLOGY - Fincolo, Daniele Amanda; Rodrigues, Gilberto Aparecido; Soares, Nathalia Maria (Revista Interface Tecnológica, 2022)
Urban growth normally takes place from the center to the surrounding suburban regions, making it an often-continuous feat of growth that can also happen from the city to the nearest rural areas. It is important to understand that the city refers to the inner urban area of ​​a municipality, and the countryside to the rural area, so that some municipalities have a completely urban or totally rural area. The objective of this work is to verify the urban growth in the district of Guariroba, municipality of Taquaritinga-SP, in the years 2003/4 and 2022. The methodology used in this study was the use of satellite images, available in the free software Google Earth Pro (GEP). Changes in land use and occupation were observed in the period considered, where woody crops (Genus Citrus) were replaced by sugarcane crops, causing changes in the rural landscape.
Keywords: Urban growth; Rural districts; Urban geography; Google Earth Pro